Distance Learning Methods in Learning in Vocational High Schools - Andy Prasetyo Wati; Sri Handayani; Jefry Aulia Martha; Mokhammad Nurruddi Zanky (STAI Miftahul Ula Nganjuk, 2022)
This research aims to find out how to optimize the use of distance learning methods in supporting students' cognitive abilities to continue optimal during self-learning at home. So, to answer the problem, researchers will use two indicator instruments, is distance learning to cognitive students and technological pedagogical content knowledge (TPACK) to the cognitive students. While the method used in this study is a survey method because there needs to be testing and proving how to distance learning and technological pedagogical content knowledge (TPACK). The dependent variables to the study are cognitive students (SC) and the independent variables are distance learning (DL) and technological pedagogical content knowledge (TPACK). There to answer the problem requires comprehensive data collection. This study used a saturated sampling of about 197 teachers obtained from SMK Pawyatan Daha 1 Kediri, SMK PGRI 2 Kediri, and SMKN 1 Bondowoso. Determination of population sampling and samples used in this study because the three places have implemented technology-based distance learning that using virtual meeting media (google classroom, zoom or google meet) and non-virtual meeting media (WhatsApp, telegram, youtube, etc.) as a balanced complement in the face of self-study policies by students. Data collection was conducted from June to October 2020 by adopting an online questionnaire. The results of theoretical and statistical studies concluded that distance learning was carried out in all three vocational high schools (SMK Pawyatan Daha 1 Kediri, SMK PGRI 2 Kediri, and SMKN 1 Bondowoso). Able to affect the cognitive abilities of students, especially when combined with the ability of teachers in master technology, content, and classes. Therefore, the two components should not be separated in supporting the success of distance learning, so that the achievement of goals in improving cognitive students can be done optimally.